Bapak jang Telah Mendahului ke Alam Baka: Kemangkatan Jenderal Sudirman dalam Kenangan Tentara, Publik, dan Rezim - Satrio Dwicahyo (Lembaran Sejarah, 2022)
As a national hero, the biography of General Sudirman has been extensively written. Like other biographical works, most of Sudirman’s biographies are concluded with his death. However, as a grand figure, Sudirman’s departure left empty spaces that prompted people to commemorate him. The commemorations did not only serve melancholic but rather pragmatic purposes. Shortly after he passed away in 1950, the Indonesian army began to narrate Sudirman’s death as a method to unite the divided officer corps. Although Sudirman was a Japanese-trained officer, he managed to maintain peaceful relations between Indonesian officers who received training under the Dutch (KNIL) and the Japanese (PETA) military. Although he has passed away, the army remained to utilize his “post-mortem” influence to mediate the peaked conflict between two factions. “Bringing Sudirman into alive” successfully ended the KNIL-PETA friction but was unable to prevent the follow-up conflict. Sukarno and Suharto also utilized Sudirman’s name to pursue their respective political interests. Sukarno positioned Sudirman as the champion of nationalism under the framework of Nationalism-Religion-and Communism or Nasakom ideology. For Suharto, Sudirman’s fame was useful to alter the influence of Sukarno, his archrival. This article combines a biographical approach with obituary writing. The present study accessed newspapers, magazines, and radio news as primary sources and complemented it with secondary literature.